The genome sequence of the European golden eagle, Aquila chrysaetos chrysaetos Linnaeus 1758. - Mead, Dan; Ogden, Rob; Meredith, Anna; Peniche, Gabriela; Smith, Michelle; Corton, Craig; Oliver, Karen; Skelton, Jason; Betteridge, Emma; Doulcan, Jale; Holmes, Nadine; Wright, Victoria; et al. (F1000 Research Ltd, 2021)
We present a genome assembly from an individual female Aquila chrysaetos chrysaetos (the European golden eagle; Chordata; Aves; Accipitridae). The genome sequence is 1.23 gigabases in span. The majority of the assembly is scaffolded into 28 chromosomal pseudomolecules, including the W and Z sex chromosomes.